Higher Education Policy Analysis: the Transformation of IAIN to UIN for the Period 2002-2017 in the Ministry of Religious Affairs of the Republic of Indonesia - Arifin, Nur (Program Pascasarjana Universitas Ibrahimy, 2021)
This article examines the transformation policy of IAIN to UIN by the Directorate of Islamic Religious Higher Education (Dit. Diktis) of the Directorate General of Islamic Education (Ditjen Pendis) of the Ministry of Religious Affairs (Kemenag) of the Republic of Indonesia. Specifically, this article describes in depth the background and policy objectives of Dit. Diktis in the transformation of IAIN to UIN; and the implementation of the transformation policy of IAIN to UIN at Dit. Diktis of the Ministry of Religious Affairs from 2002 to 2017. This study used a qualitative method with the type of case study research. Data collection techniques consist of observation method, in-depth interview, and documentation. While data analysis techniques include: data reduction, data presentation, verification, and concluding. Checking the validity of the data consists of credibility, transferability, dependability, and confirmability. The results of this study found that the basic policy formulation for the transformation of IAIN to UIN occurred in different contexts and situations for three periods. They are: 1) the first period, 2002-2005 (6 UIN), 2) the second period, 2013-2015 (5 UIN), and 3) The third period, 2017 (6 UIN).